Correlation between Microstructure of Copper Oxide Thin Films and Its Gas Sensing Performance at Room Temperature - Nayan, N; Sandan, MZ; Wei, LJ; Ahmad, MK; Lias, J; Fhong, SC; Shakaff, AYM; Zakaria, A; Zain, AFM (Elsevier Science Bv, 2024)
Indexed by WOS